2012
DOI: 10.2355/tetsutohagane.98.469
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Microstructure in Thick Steel with High Voltage TEM

Abstract: 緒言Bulk specimen is of big advantage for studying internal microstructures because true strained state of materials is to be easily relaxed in thin specimen and then various micro structural factors that control mechanical properties are subjected to change. In this study, HVEM, 1250kV acceleration voltage, was applied to study microstructure in high strength steels using specimens over several 100nm thicknesses. In addition to improving transparency of incident electron, reducing chromatic and stigmatic aberra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…However, it is also demonstrated that in these two samples an increase in the dislocation density becomes slow in the later stage of deformation, indicating that dynamic recovery occurs significantly [22]. Similar tendency in dislocation structure development has been observed in low carbon steels with nano-sized (Ti,Mo)C particles [22,42].…”
Section: Dislocation Structuressupporting
confidence: 57%
“…However, it is also demonstrated that in these two samples an increase in the dislocation density becomes slow in the later stage of deformation, indicating that dynamic recovery occurs significantly [22]. Similar tendency in dislocation structure development has been observed in low carbon steels with nano-sized (Ti,Mo)C particles [22,42].…”
Section: Dislocation Structuressupporting
confidence: 57%
“…In the Ti-added sample transformed for 0.5 h having the average carbide diameter of 5.5 nm, a quite uniform dislocation structure is observed even after 1% of strain, and the dislocation density is already high. Yamada et al 47) observed the dislocation structure after 0.2% plastic strain of the steel with nanosized (Ti,Mo)C particles and found a high density of dislocations with a uniform distribution in the ferrite matrix, corresponding well with the resent observation. Tensile deformation of 5% strain leads to a higher density of dislocations in the Ti-added steel, but the dislocation distributions is quite uniform.…”
Section: Work Hardening Behavior and Ductilitymentioning
confidence: 52%
“…17) Yamada et al confirmed the suppression of dislocation slip in Ti-and Mo-added steel by measuring the breaking angles and the particle distances using in-situ tensile testing in TEM. 18) In-situ tensile experiment is capable of observing the movements of dislocations and particles dynamically, so that the it is the method to elucidate the dispersion strengthening mechanisms.…”
Section: )mentioning
confidence: 99%